2019
DOI: 10.1111/jjns.12293
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for postpartum urinary retention after vaginal delivery in Japan: A case‐control study

Abstract: Aim This study aimed to clarify the prevalence and risk factors of postpartum urinary retention after vaginal delivery. It also described the healing process of women who had postpartum urinary retention. Methods In this case‐control study, 77 women who had postpartum urinary retention were matched by age and parity with 385 women as controls. Data were analyzed by conditional logistic regression analysis. Data were collected from the women in the case group regarding their healing process and conditions for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 18 publications
3
24
0
1
Order By: Relevance
“…In the present study, episiotomy and second-degree perineal tears were both identified as independent risk factors for PUR, which is in line with the findings of previous studies [ 6 , 19 , 27 , 30 , 31 ]. In a systematic review by Mulder et al [ 12 ], episiotomy was found to be directly related to PUR.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, episiotomy and second-degree perineal tears were both identified as independent risk factors for PUR, which is in line with the findings of previous studies [ 6 , 19 , 27 , 30 , 31 ]. In a systematic review by Mulder et al [ 12 ], episiotomy was found to be directly related to PUR.…”
Section: Discussionsupporting
confidence: 93%
“…In the past 20 years, the incidence of overt PUR has been reported to be as low as 0.14% [ 18 ], while Gema et al reported a higher incidence of 9.85% [ 14 ]. This large variation in morbidity may be due to the different definitions of overt PUR and inclusion criteria, such as including women who deliver via caesarean section [ 19 ]. Compared with primiparas, multiparas who have a shorter labour process, and lower rates of analgesic delivery, and proportions of instrument-assisted delivery may have a higher incidence of PUR [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The final review includes one systematic review, 11 one multicentre randomized controlled clinical trial, 13 five retrospective casecontrol studies, [14][15][16][17][18] one retrospective medical review, 19 two retrospective analysis, 20,21 two prospective observational studies, 22,23 two case-control studies, 24,25 one prospective before-after study, 26 one cross-sectional study 27 and one clinical practice guideline. 28…”
Section: Resultsmentioning
confidence: 99%
“…Study conducted by Izumi Kawasoe in Japan and reported prevalence of postpartum urinary retention was 1.2%. 24…”
Section: Discussionmentioning
confidence: 99%